2006
DOI: 10.1093/annonc/mdj039
|View full text |Cite
|
Sign up to set email alerts
|

Single agent carboplatin for CS IIA/B testicular seminoma. A phase II study of the German Testicular Cancer Study Group (GTCSG)

Abstract: Four cycles of single agent carboplatin AUC 7 do not safely eradicate retroperitoneal metastases in patients with stage IIA/B seminoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0
4

Year Published

2006
2006
2018
2018

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 77 publications
(32 citation statements)
references
References 20 publications
0
26
0
4
Order By: Relevance
“…However, the relationship among the dose intensity, total number of cycles, and treatment outcome (including the rate of relapse) is very controversial. [4][5][6][7][8]16 Although there is no strict evidence for the efficacy of prolonged administration of carboplatin, including maintenance therapy, long-term carboplatin at 4 AUC may achieve therapeutic efficacy with minimal occurrence of serious adverse events.…”
Section: Discussionmentioning
confidence: 99%
“…However, the relationship among the dose intensity, total number of cycles, and treatment outcome (including the rate of relapse) is very controversial. [4][5][6][7][8]16 Although there is no strict evidence for the efficacy of prolonged administration of carboplatin, including maintenance therapy, long-term carboplatin at 4 AUC may achieve therapeutic efficacy with minimal occurrence of serious adverse events.…”
Section: Discussionmentioning
confidence: 99%
“…Giannis et al [28] also concluded that patients with low-volume metastatic stage IIA and IIB seminoma can be treated by 4 cycles of PEB instead of radiotherapy with the risk of diverse toxicity effect. A different chemotherapy strategy was studied by Krege et al [29], investigating the use of single-agent carboplatin at a dose of AUC 7 in 108 patients with seminoma stages IIA (3 cycles) and IIB (4 cycles). Complete response, partial response, no response and progressive disease were displayed in 81, 16, 2 and 1%, prospectively.…”
Section: Discussionmentioning
confidence: 99%
“…Complete response, partial response, no response and progressive disease were displayed in 81, 16, 2 and 1%, prospectively. Therefore, single-agent carboplatin chemotherapy (4 cycles) did not sufficiently eliminate retroperitoneal metastases and was not recommended in stage IIA/IIB seminoma [29]. Combining carboplatin and radiotherapy for seminoma stage IIA/IIB appears to have additional toxicity, but reduces the relapse rate on long-term follow-up with a 5-year relapse-free survival of 92.3% (stage IIA) and 100% (stage IIB) compared to radiotherapy alone (5-year relapse-free survival of 84.9% in stage IIA and 69.4% in stage IIB) [30].…”
Section: Discussionmentioning
confidence: 99%
“…Hier zeigte sich hinsichtlich der Rezidivrate kein Vorteil gegenüber der Bestrahlung [15]. Als ungünstig erwies sich, dass nahezu alle Rezidive die primären Metastasenlokalisationen betrafen, wohingegen Rezidive nach Bestrahlung in der Regel außer-halb des Bestrahlungsfeldes auftreten [3].…”
Section: Seminom Cs Iia/bunclassified